Outcome of Trans-obturator Tape Procedure in the treatment of Stress Urinary Incontinence at Kathmandu Model Hospital - Shrestha, Ranjana; Dangal, Ganesh; Bharati, Sonu; Karki, Aruna; Pradhan, Hema Kumari; Bhattachan, Kabin; Poudel, Rekha; Bajracharya, Nishma; Tiwari, Kenusha Devi (Nepal Journal of Obstetrics and Gynaecology, 2020)
Aims: To evaluate the improvement in the quality of life of women with stress urinary incontinence who were treated with trans-obturator tape procedure.Methods: This is a cross-sectional study of treatment of stress urinary incontinence using trans-obturator tape at Kathmandu Model Hospital from February 2018 to December 2019. The outcome of the procedure in terms of improvement in quality of life and surgical complications were assessed.Results: Out of 16 cases of stress urinary incontinence half of them were post-menopausal. One each had intra-operative bladder injury, urinary retention and urinary tract infection; 14 cases improved completely by a week, one had some improvement and one didn’t improve. At six months follow-up one case had no improvement and one developed urge incontinence.Conclusions: Trans-obturator tape has been found a good procedure for the treatment of stress urinary incontinence in our setting and hence led to high rate of improvement in quality of life with minimal and minor complications.Key words: Complications; quality of life; stress urinary incontinence; trans-obturator tape